Ventilation heterogeneity imaged by multibreath wash‐ins of hyperpolarized 3He and 129Xe in healthy rabbits. (10th August 2021) - Hamedani, Hooman; Kadlecek, Stephen; Ruppert, Kai; Xin, Yi; Duncan, Ian; Rizi, Rahim R.
Abstract : Key points: Multibreath imaging to estimate regional gas mixing efficiency is superior to intensity‐based single‐breath ventilation markers, as it is capable of revealing minute but essential measures of ventilation heterogeneity which may be sensitive to subclinical alterations in the early stages of both obstructive and restrictive respiratory disorders. Large‐scale convective stratification of ventilation in central‐to‐peripheral directions is the dominant feature of observed ventilation heterogeneity when imaging a heavy/less diffusive xenon gas mixture; smaller‐scale patchiness, probably originating from asymmetric lung function at bronchial airway branching due to the interaction of convective and diffusive flows, is the dominant feature when imaging a lighter/more diffusive helium gas mixture. Since detecting low regional ventilation is crucial for characterizing diseased lungs, our results suggest that dilution with natural abundance helium and imaging at higher lung volumes seem advisable when imaging with hyperpolarized 129 Xe; this will allow the imaging gas to reach slow‐filling and/or non‐dependent lung regions, which might otherwise be impossible to distinguish from total ventilation shunt regions. The ability to differentiate these regions from those of total shunt is worse with typical single‐breath imaging techniques. Abstract: The mixing of freshly inhaled gas with gas already present in the lung can be directly assessed with heretofore unachievable precision via magnetic resonance imaging of signal build‐up resulting from multiple wash‐ins of a hyperpolarized (HP) gas. Here, we used normoxic HP 3 He and 129 Xe mixtures to study regional ventilation at different spatial scales in five healthy mechanically ventilated supine rabbits at two different inspired volumes. To decouple the respective effects of density and diffusion rates on ventilation heterogeneity, two additional studies were performed: one in which 3 He was diluted with an equal fraction of natural abundance xenon, and one in which 129 Xe was diluted with an equal fraction of 4 He. We observed systematic differences in the spatial scale of specific ventilation heterogeneity between HP 3 He and 129 Xe. We found that large‐scale, central‐to‐peripheral convective ventilation inhomogeneity is the dominant cause of observed heterogeneity when breathing a normoxic xenon gas mixture. In contrast, small‐scale ventilation heterogeneity in the form of patchiness, probably originating from asymmetric lung function at bronchial airway branching due to interactions between convective and diffusive flows, is the dominant feature when breathing a normoxic helium gas mixture, for which the critical zone occurs more proximally and at an imageable spatial scale. We also showed that the existence of particular underventilated non‐dependent lung regions when breathing a heavy gas mixture is the result of the density of that mixture – rather than, for example, its diffusion rate or viscosity. Finally, we showed that gravity‐dependent ventilation heterogeneity becomes substantially more uniform at higher inspired volumes for xenon gas mixtures compared to helium mixtures. Key points: Multibreath imaging to estimate regional gas mixing efficiency is superior to intensity‐based single‐breath ventilation markers, as it is capable of revealing minute but essential measures of ventilation heterogeneity which may be sensitive to subclinical alterations in the early stages of both obstructive and restrictive respiratory disorders. Large‐scale convective stratification of ventilation in central‐to‐peripheral directions is the dominant feature of observed ventilation heterogeneity when imaging a heavy/less diffusive xenon gas mixture; smaller‐scale patchiness, probably originating from asymmetric lung function at bronchial airway branching due to the interaction of convective and diffusive flows, is the dominant feature when imaging a lighter/more diffusive helium gas mixture. Since detecting low regional ventilation is crucial for characterizing diseased lungs, our results suggest that dilution with natural abundance helium and imaging at higher lung volumes seem advisable when imaging with hyperpolarized 129 Xe; this will allow the imaging gas to reach slow‐filling and/or non‐dependent lung regions, which might otherwise be impossible to distinguish from total ventilation shunt regions. The ability to differentiate these regions from those of total shunt is worse with typical single‐breath imaging techniques.